Low-cost Wireless Personal Weather Station for Rural Farmers - Tchamda, André Rodrigue; Djousse K., Merlain Boris; Koumetio, Anselme Maffo; Fonteh, Mathias Fru; Pelap, François Becau; Tchitnga, Robert; Kom, Martin (Discoveries in Agriculture and Food Sciences, 2021)
This document presents the design of a prototype of a low-cost personal weather station suitable for farmers in rural areas who are or may not be engaged in rudimentary agriculture. This prototype measure several weather data: temperature, relative humidity, wind speed, wind direction, rainfall. For further data analysis, these are transmitted for recording to a remote server via wireless communication. The server offers data extraction possibilities in multiple file formats. A prototyping of the personal weather station is designed and commissioned. An extract of the results over two days is presented in the results section of this document